2013
DOI: 10.1002/eji.201343671
|View full text |Cite
|
Sign up to set email alerts
|

Invariant chain as a vehicle to load antigenic peptides on human MHC class I for cytotoxic T‐cell activation

Abstract: IntroductionSuccessful vaccination depends on activation of CD8 + and CD4 + T-cell responses by presentation of antigenic peptides in the context of major histocompatibility complex class I (MHCI) and II Correspondence: Dr. Tone F. Gregers e-mail: t.f.gregers@ibv.uio.no (MHCII) molecules, respectively. The processing and subsequent presentation of antigenic peptides by MHCI or MHCII molecules on the surface of antigen presenting cells (APCs) requires a coordinated action of different accessory molecules and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…The li, a 33 kDa polypeptide, is involved in the stabilization and proper folding of HLA class II antigens as well as in the prevention of binding cellular peptides on HLA class II antigens, while it could also serve as vehicle to load antigenic peptides on MHC class I molecules. 15 In addition, the li facilitates the export of HLA class II molecules from the ER and is responsible for directing the HLA class II complexes into specialized endosomal/lysosomal antigen loading compartments, termed MHC class II containing compartment (MIIC). Here, the li is proteolytically degraded by cathepsin into the 14 amino acid long class II-associated invariant chain peptide (CLIP) occupying the HLA class II peptide-binding groove.…”
Section: Organization Of the Hla Class II Antigen-processing Machinerymentioning
confidence: 99%
“…The li, a 33 kDa polypeptide, is involved in the stabilization and proper folding of HLA class II antigens as well as in the prevention of binding cellular peptides on HLA class II antigens, while it could also serve as vehicle to load antigenic peptides on MHC class I molecules. 15 In addition, the li facilitates the export of HLA class II molecules from the ER and is responsible for directing the HLA class II complexes into specialized endosomal/lysosomal antigen loading compartments, termed MHC class II containing compartment (MIIC). Here, the li is proteolytically degraded by cathepsin into the 14 amino acid long class II-associated invariant chain peptide (CLIP) occupying the HLA class II peptide-binding groove.…”
Section: Organization Of the Hla Class II Antigen-processing Machinerymentioning
confidence: 99%
“…The cloning strategy is shown in Figure 1A. 21 Briefly, cDNA was tagged with a poly-C tail using a terminal transferase reaction. The V regions were amplified using a common poly-GI forward primer (pGI: 59-CACCGGGIIGGGIIGGGII-39) and 2 different sets of human constant region-specific reverse primers (pC1 and pC2: pCa1, 59-AGTCAGATTTG TTGCTCCAGGCC-39; pCb1, 59-TTCACCCACCAGCTCAGCTCC-39; pCa2, 59-ATACGCGTTCTCTCAGCTGGTACACGG-39; pCb2, 59-ATACGCG TAGATCTCTGCTTCTGATGGC-39).…”
Section: Identification and Generation Of A Recombinant Tcr Recognizimentioning
confidence: 99%
“…Kim et al [23] found that the combination of CIITA DNA with Ii-PADRE DNA (Ii linked to the pan-HLA-DR-reactive epitope) and calreticulin (CRT)/E6 (co-administration of DNAencoding CRT linked to human papillomavirus 16 E6 Ag) enhanced E6-specific CD8þ T cell immune responses and represents a potentially effective method to combat tumours in clinical settings. CLIP-replaced Ii efficiently activated Ag-specific CD8þ T cells independent of the classical MHC I peptide-loading machinery [24]. Ii-Key, the core fragment of Ii, has been shown to facilitate direct loading of MHC class II epitopes onto the peptidebinding groove [6,25,26].…”
Section: Discussionmentioning
confidence: 99%